The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0140786
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Anti-Angiogenic and Anti-Oncogenic Activities of the Novel Mithralog Demycarosyl-3D-ß-D-Digitoxosyl-Mithramycin SK (EC-8042)

Abstract: Demycarosyl-3D-ß-D-digitoxosyl-mithramycin SK (DIG-MSK) is a recently isolated analogue of mithramycin A (MTA) that showed differences with MTA in the DNA binding strength and selectivity. These differences correlated with a better therapeutic index and less toxicity in animal studies. Herein, we show that DIG-MSK displays a potent anti-tumor activity against different types of cancer cell lines, ovarian tumor cells being particularly sensitive to this drug. Of relevance, DIG-MSK exerts low toxicity on fibrobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Recently, the new mithralog demycarosyl-3D-β-D-digitoxosyl-mithramycin SK (EC-8042; DIG-MSK) has been obtained and characterized [ 17 ]. As expected, EC-8042 preferentially binds GC-rich sequences, is a potent inhibitor of SP-driven gene expression and shows pleiotropic anti-angiogenic and anti-oncogenic activities [ 18 20 ]. EC-8042 altered the expression of cell cycle related genes resulting in cell cycle arrest and apoptosis in breast cancer cell lines [ 21 ].…”
Section: Introductionmentioning
confidence: 72%
“…Recently, the new mithralog demycarosyl-3D-β-D-digitoxosyl-mithramycin SK (EC-8042; DIG-MSK) has been obtained and characterized [ 17 ]. As expected, EC-8042 preferentially binds GC-rich sequences, is a potent inhibitor of SP-driven gene expression and shows pleiotropic anti-angiogenic and anti-oncogenic activities [ 18 20 ]. EC-8042 altered the expression of cell cycle related genes resulting in cell cycle arrest and apoptosis in breast cancer cell lines [ 21 ].…”
Section: Introductionmentioning
confidence: 72%
“…Mithramycin and additional analogs demonstrated rapid intracellular accumulation in OVCAR-3 cell lines [ 38 ]. The IC 50 values of mithramycin and related compounds were in the low-nanomolar range in OVCAR-3 cell cultures, induce cell arrest in G1 [ 70 ]. This finding raises the possibility of mithramycin or its analog as a potential treatment for chemotherapy-resistant ovarian cancer, particularly platinum-resistant cancer.…”
Section: Sp1mentioning
confidence: 99%
“…One of the most promising mithralogs, demycarosyl-3D-betat-D-digitoxosyl-mithramycin SK (MTM-DIG-MSK or EC-8042), has demonstrated retained anti-tumor properties, including in vitro ovarian cancer lines, but reduced in vitro toxicity in fibroblasts and mononuclear blood cells, compared to mithramycin [ 37 , 40 , 70 , 82 ]. Mithramycin and EC-8042 reduced the viability and invasiveness of malignant melanoma cell lines [ 85 ].…”
Section: Development Of Mithramycin Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a functional study, it was found that two new analogs of MTA, namely MTMSDK and MTM-SK, hindered the growth of OC cells in xenografts via inhibition of Sp1-based transcription [87]. Another efficient analog of MTA is demycarosyl-3D-ß-D-digitoxosyl-mithramycin SK (DIG-MSK), as it can inhibit Sp1-mediated transcription, mRNA expression, and various other genes regulated by Sp1 that have a pivotal role in OC, like VEGFA, BCL2L1 (Bcl-2-like 1; Bcl-XL), human telomerase Reverse Transcriptase (hTERT), BRCA2, and MYC [88]. Similar to this study, Vizcaino et al also observed that DIG-MSK can downregulate the binding of Sp1 to pro-oncogenes in OC cells [89].…”
Section: Sp1 As a Therapeutic Target In Ocmentioning
confidence: 99%